Decreased ANT content in Zucker fatty rats: Relevance for altered hepatic mitochondrial bioenergetics in steatosis - Teodoro, João (2006)
Mitochondria from Zucker fatty (ZF) rats (a model for fatty liver disease) showed a delay in the repolarization after a phosphorylative cycle and a decrease on state 3 respiration, suggesting alterations at the phosphorylative system level. The ATPase activity showed no differences between control and ZF rats, implying alterations in other components of the phosphorylative system. A pronounced depletion in the content of the adenine nucleotide translocator (ANT) was observed by Western blotting, while no alterations were found in the mitochondrial voltage-dependent anion channel content. These data suggest that hepatic accumulation of fat impairs mitochondrial function, reflecting the loss of oxidative phosphorylation capacity caused by a decrease in the ANT content.